Kinerja Daya Saing Teh Indonesia di Pasar Internasional: Analisis Data Sekunder - Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto; Sugiyarto; Setiawan Suryo K. J. (Journal of World Trade Studies, 2012)
The purpose of this study is (1) to know the trend of tea production in several tea producing countries (2) to determine the trend of Indonesian tea export and (3) to determine the competitiveness of Indonesian tea in the international market. The data used in this study is a secondary data that analyzed with descriptive methods. Both the first and the second objectives of this study are analyzed by using the trend equation models with Least Square method. In determining the competitiveness of Indonesian tea, this study employs four analysis tools: RCA, RSCA, AR, and ISPs. The results show that (1) the trend of tea production in China, India, Sri Lanka, Kenya and Indonesia has increased from year to year (2) the trend of Indonesian tea export increased from year to year and (3) the competitiveness of Indonesian tea based on RCA shows that Indonesian tea commodity has a greater market share than the share of the world tea market. The RSCA index shows that Indonesian tea commodity has a comparative advantage thus eligible to be traded in the international market. The value ofAR suggests that the accelerated growth of Indonesian tea export commodities has not been able to follow the accelerated growth of tea imports in the world. Based on the number of ISP Indonesian tea commodities in the international market has reached the stage of maturation.